2006
DOI: 10.1007/s11524-006-9060-7
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering: A Physical Activity Intervention for Older Adults—The Experience Corps® Program in Baltimore

Abstract: There is compelling evidence supporting the benefits of increased regular physical activity in older adults. The Experience Corps program in Baltimore MD was designed in part as a community based approach to increasing physical activity that would also appeal to older adults who have historically not utilized health promotion programs. The Baltimore Experience Corps program places older volunteers in public elementary schools for 15 h a week in roles designed to improve the academic outcomes of children and, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 44 publications
(43 reference statements)
3
94
0
Order By: Relevance
“…The height of the bar indicates the strength of the study design. 115,120,123 suggesting that these group programmes are less effectivene, and, therefore, there is less consistency in strength of evidence for group interventions in these populations. Apart from this difference, these studies with older/younger mean age participants echo the findings of the A1/A2 studies in tending to report positive outcomes for all intervention types.…”
Section: Figurementioning
confidence: 99%
“…The height of the bar indicates the strength of the study design. 115,120,123 suggesting that these group programmes are less effectivene, and, therefore, there is less consistency in strength of evidence for group interventions in these populations. Apart from this difference, these studies with older/younger mean age participants echo the findings of the A1/A2 studies in tending to report positive outcomes for all intervention types.…”
Section: Figurementioning
confidence: 99%
“…The few studies that did focused on physical activity and cognitive functioning in older adults [18][19][20] or teen pregnancies and academic failure in adolescents. 21,22 Hence, the finding that interventions that get adolescents to volunteer can change cardiovascular risk markers has important implications for health in the adolescent years and beyond.…”
Section: Commentmentioning
confidence: 99%
“…Samples comprised mostly middle-aged women; however, 2 studies had mean ages of 65 or older. 5,6 Several studies were specifically designed for participants with chronic illnesses 6 such as diabetes (n = 5), hypertension (n = 3), and breast cancer, and 3 focused on obese participants. But regardless of recruitment efforts, numerous studies reported mostly overweight/obese (n = 16) and hypertensive (n = 9) samples.…”
Section: Sample and Attrition Issuesmentioning
confidence: 99%